Effects of ZrO2 on the Performance of CuO-ZnO-TiO2-ZrO2 Catalysts Used in Methanol Synthesis from CO2 Hydrogenation - Zhao, Yunpeng; Jia, Lihua; Jing, Tao; Sun, Dezhi; Shik Chung, Jong (Asian Journal of Chemistry, 2012)
CuO-ZnO-TiO2-ZrO2 catalysts were prepared by a parallel-slurry-mixing-precipitation method combined with addition of surfactant. Characterization and performance of the catalysts were investigated by BET, XRD, SEM, H2-TPR and methanol synthesis from CO2 hydrogenation. Carbon dioxide conversion and methanol selectivity were found to increase with increasing ZrO2 content on catalysts. The results show that CuO-ZnO-TiO2-ZrO2 (2:1:2:1 molar ratio) catalyst exhibited an optimum catalytic performance.